Spontaneous Rupture of Urinary Bladder: Two Case Reports and Review of Literature - Zhang, Yue; Yuan, Shuo; Alshayyah, Rami W. A.; Liu, Wankai; Yu, Yang; Shen, Chen; Lv, Hang; Wen, Lijie; He, Yi; Yang, Bo (Frontiers in Surgery, 2021)
Objectives: Spontaneous rupture of the urinary bladder (SRUB) is extremely rare and might be misdiagnosed, leading to a high mortality rate. The current study aimed to identify the cause, clinical features, and diagnosis strategy of SRUB. Methodology: We presented a case report for two women (79 and 63 years old) misdiagnosed with acute abdomen and acute kidney injury, respectively, who were finally confirmed to have SRUB by a series of investigations and exploratory surgery. Meanwhile, literature from multiple databases was reviewed. PubMed, the Chinese National Knowledge Infrastructure (CNKI), the Chinese Biological Medical Literature Database (CBM), WANFANG DATA, and the Chongqing VIP database for Chinese Technical Periodicals (VIP) were searched with the keywords “spontaneous bladder rupture” or “spontaneous rupture of bladder” or “spontaneous rupture of urinary bladder.” All statistical analyses were conducted using SPSS 20.0 software. Results: A total of 137 Chinese and 182 English literature papers were included in this article review. A total of 713 SRUB patients were analyzed, including the two patients reported by us. The most common cause of SRUB was alcohol intoxication, lower urinary tract obstruction, bladder tumor or inflammation, pregnancy-related causes, bladder dysfunction, pelvic radiotherapy, and history of bladder surgery or bladder diverticulum. Most cases were diagnosed by exploratory laparotomy and CT cystography. Patients with extraperitoneal rupture could present with abdominal pain, abdominal distention, dysuria, oliguria or anuria, and fever. While the main symptoms of intraperitoneal rupture patients could be various and non-specific. The common misdiagnoses include acute abdomen, inflammatory digestive disease, bladder tumor or inflammation, and renal failure. Most of the patients (84.57%) were treated by open surgical repair, and most of them were intraperitoneal rupture patients. Overall, 1.12% of patients were treated by laparoscopic surgery, and all of them were intraperitoneal rupture patients. Besides, 17 intraperitoneal rupture patients and 6 extraperitoneal rupture patients were treated by indwelling catheterization and antibiotic therapy. Nine patients died of delayed diagnosis and treatment. Conclusions: SRUB often presents with various and non-specific symptoms, which results in misdiagnosis or delayed treatment. Medical staff noticing abdominal pain suggestive of peritonitis with urinary symptoms should be suspicious of bladder rupture, especially in patients with a history of bladder disease. CT cystography can be the best preoperative non-invasive examination tool for both diagnosis and evaluation. Conservative management in the form of urine drainage and antibiotic therapy can be used in patients without severe infection, bleeding, or major injury. Otherwise, surgical treatment is recommended. Early diagnosis and management of SRUB are crucial for an uneventful recovery.